2017
DOI: 10.3389/fnins.2017.00273
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from NSC-34 Cells Transfected with hSOD1-G93A Are Enriched in miR-124 and Drive Alterations in Microglia Phenotype

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal adult-onset neurodegenerative disorder affecting motor neurons (MNs). Evidences indicate that ALS is a non-cell autonomous disease in which glial cells participate in both disease onset and progression. Exosomal transfer of mutant copper-zinc superoxide dismutase 1 (mSOD1) from cell-to-cell was suggested to contribute to disease dissemination. Data from our group and others showed that exosomes from activated cells contain inflammatory-related microRNAs (inflamma-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 129 publications
4
118
3
Order By: Relevance
“…Its forced expression downregulates pro‐inflammatory markers, while increases the expression of protective markers, as is the case of TGF‐β, Arg1, and FIZZ1 (Y. Sun et al, ; Ponomarev et al, ; S. Huang et al, ; Periyasamy et al, ) and reduces microglial phagocytic ability (Pinto, Cunha, Barbosa, Vaz, & Brites, ; Svahn, Giacomotto, Graeber, Rinkwitz, & Becker, ). The contribution of miR‐124 to homeostatic/anti‐inflammatory microglia functions relies on silencing of CCAAT/enhancer‐binding protein (C/EBP)‐α (P. Zhang et al, ), one of the major transcription factor that drives pro‐inflammatory microglia polarization (A. Yu et al, ).…”
Section: Micrornas Promoting Pro‐regenerative Microglia Phenotype Andmentioning
confidence: 99%
“…Its forced expression downregulates pro‐inflammatory markers, while increases the expression of protective markers, as is the case of TGF‐β, Arg1, and FIZZ1 (Y. Sun et al, ; Ponomarev et al, ; S. Huang et al, ; Periyasamy et al, ) and reduces microglial phagocytic ability (Pinto, Cunha, Barbosa, Vaz, & Brites, ; Svahn, Giacomotto, Graeber, Rinkwitz, & Becker, ). The contribution of miR‐124 to homeostatic/anti‐inflammatory microglia functions relies on silencing of CCAAT/enhancer‐binding protein (C/EBP)‐α (P. Zhang et al, ), one of the major transcription factor that drives pro‐inflammatory microglia polarization (A. Yu et al, ).…”
Section: Micrornas Promoting Pro‐regenerative Microglia Phenotype Andmentioning
confidence: 99%
“…Several reports demonstrated that TLR signalling inhibits phagocytosis of apoptotic cells through activation of the NFkB pathway in macrophages (Deng et al, ; X. Feng et al, ). Another recent study showed that exosomes derived from the NSC‐34 motoneurons expressing mutant SOD1 (G93A) induced sustained NFkB activation and loss of phagocytic ability in N9 microglial cells (Pinto, Cunha, Barbosa, Vaz, & Brites, ). On the other hand, TLR2 and TLR4/CD14 complexes are also involved in recognition and uptake of different pathogens into microglial cells (Janda, Boi, & Carta, ; Stefanova et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Selective enrichments of miRs in exosomes were due to the alterations in parental or donor cells, from which exosomes are secreted or originated . Of note, exosomes take part in cellular behaviour changes, such as phenotype transition and inflammatory reactions via transporting miRs to interfere with several signalling pathways . Uptake of exosomes by osteoblasts is accelerated by increased receptors expressed on the cell surface, with transporting miRs from osteoclasts under osteoclastogenesis stimulation .…”
Section: Exosomes Participate In Vcmentioning
confidence: 99%